Repeated large scale loop migrations of an adult European Honey Buzzard (Avocetta, 2019)
During migration, birds adopt flight strategies that often differ between spring and autumn. This behaviour can lead to differences in migratory paths as well as in-flight performances between seasons and may help to explain seasonal differences in the numbers of birds passing through migratory bottlenecks. Visual observations have revealed that larger numbers of adult European Honey Buzzards Pernis apivorus pass through the Central Mediterranean region during spring rather than during autumn migration, while the opposite occurs at the Strait of Gibraltar. It suggested that substantial numbers of birds, probably belonging to the population breeding in eastern Europe, use an anticlockwise loop migration performing a risk-minimization strategy during autumn and a time minimization strategy during spring migration to maximize their fitness. In this study, we analyze for the first time three autumn and three spring migrations of an adult bird belonging to this population tracked by satellite telemetry, also in relation to wind conditions. Each year the bird used the large-scale loop migration between the breeding site located in northern Hungary and the wintering ground in northern Cameroon, showing a higher overall migration speed, shorter paths and longer water crossings during spring movements. The bird benefited from a more efficient tailwind support during spring, while compensated the effect of lateral winds mostly at the onset of both autumn and spring migration. Finally, the bird initiated the spring sea-crossing at the same location each year but showed remarkable flexibility in route choice across the sea in response to annual differences in different wind conditions. These results support the idea that the stronger aggregation of adult European Honey Buzzards in Central Mediterranean bottlenecks in spring vs autumn largely consists of adults breeding in central-eastern Europe that return to their nesting sites along a relatively direct route.
Keywords: wind drift; water crossing; biologging; Pernis apivorus; navigation; loop migration